Heat-sealable resin composition, cured product, and laminate
The heat sealing resin composition, comprising (meth)acrylamide and specific ethylenically unsaturated monomers, along with a plasticizer, overcomes the challenge of achieving high heat seal strength at low curing temperatures, resulting in a robust cured product and laminate.
Patent Information
- Application Number
- JP2023164113
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing water-based heat-sealing resin compositions struggle to achieve high heat seal strength without applying high heat, and they cure at relatively low temperatures, resulting in a cured product with insufficient heat seal strength.
A heat sealing resin composition comprising a polymer formed from (meth)acrylamide and one or more monomers with a carboxy, sulfo, or amino group, along with a plasticizer, which allows for high heat seal strength even when cured at a relatively low temperature.
The composition achieves high heat seal strength in the cured product and laminate, even when cured at a low temperature, effectively addressing the limitations of existing technologies.
Smart Images

Figure 2025054897000001 
Figure 2025054897000002 
Figure 2025054897000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-sealable resin composition, a cured product, and a laminate. [Background technology]
[0002] In recent years, the use of aqueous resin compositions has been increasingly required from the viewpoint of reducing the environmental load. For example, aqueous heat-sealable resin compositions containing polyurethane resins have been developed for heat-sealable films (substrates coated with heat-sealable resin compositions (heat-sealing agents)) used in medical device packages and food packages (Patent Document 1).
[0003] However, with such resin compositions, it is difficult to achieve heat seal strength unless they are heated to a high temperature of 150°C. Therefore, we focused on a resin composition that can be cured at a relatively low temperature and that has a high heat seal strength. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-045313 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a heat-sealable resin composition which gives a cured product and a laminate having high heat seal strength even when cured at a relatively low temperature. [Means for solving the problem]
[0006] The present inventors have conducted extensive research and have found a way to solve the above problems, thereby completing the present invention. That is, the present invention relates to the following heat-sealable resin composition, cured product, and laminate.
[0007] 1. (Meth)acrylamide (a1), and A heat-sealable resin composition comprising a polymer (A) of a polymerization component containing one or more monomers (a2) selected from an ethylenically unsaturated monomer having a carboxy group, an ethylenically unsaturated monomer having a sulfo group, and an ethylenically unsaturated monomer having an amino group.
[0008] 2. The heat-sealable resin composition according to item 1, wherein the component (a1) is 60 to 99.5 mol % and the component (a2) is 0.1 to 30 mol % relative to 100 mol % of all polymerized components.
[0009] 3. The heat-sealable resin composition according to item 1 above, further comprising a plasticizer (B).
[0010] 4. A cured product of the heat-sealable resin composition according to any one of items 1 to 3 above.
[0011] 5. A laminate having the cured product described in item 4 above on at least one surface of a substrate. Effect of the Invention
[0012] The heat-sealable resin composition of the present invention gives a cured product or laminate having high heat seal strength even when cured at a relatively low temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The heat-sealable resin composition of the present invention contains a polymer (A) (hereinafter referred to as polymer (A)) of polymerization components including (meth)acrylamide (a1) (hereinafter referred to as component (a1)) and one or more monomers (a2) (hereinafter referred to as component (a2)) selected from ethylenically unsaturated monomers having a carboxy group, monomers having a sulfo group, and ethylenically unsaturated monomers having an amino group. Note that "(meth)acrylic" means methacryl and / or acrylic (hereinafter the same).
[0014] The component (a1) is methacrylamide or acrylamide. These may be used alone or in combination of two kinds.
[0015] The molar ratio of the (a1) component is preferably 60 to 99.5 mol %, more preferably 70 to 99.5 mol %, and even more preferably 90 to 99.5 mol %, based on 100 mol % of all polymerized components, because the cured product is likely to exhibit high heat seal strength.
[0016] The component (a2) is one or more monomers selected from an ethylenically unsaturated monomer having a carboxy group, an ethylenically unsaturated monomer having a sulfo group, and an ethylenically unsaturated monomer having an amino group, and the use of this component makes it easier to suppress thickening and gelation caused by an overreaction of the component (a1) during polymerization, etc. The ethylenically unsaturated monomer refers to a monomer that contains one or more carbon-carbon double bonds and / or carbon-carbon triple bonds.
[0017] Examples of ethylenically unsaturated monomers having a carboxy group include (meth)acrylic acid, acrylic anhydride, 2-(meth)acrylamido-N-glycolic acid, N-(meth)acryloylglycine, 3-(meth)acrylamidopropionic acid, 4-(meth)acrylamidobutanoic acid, itaconic acid, itaconic anhydride, fumaric acid, maleic acid, and maleic anhydride. The monomers may be used in the form of salts such as alkali metal salts such as sodium and potassium; ammonium salts such as ammonia; and organic amine salts such as trimethylamine, triethylamine, trimethanolamine, and triethanolamine. These may be used alone or in combination of two or more. Among these, (meth)acrylic acid and itaconic acid are preferred.
[0018] Examples of ethylenically unsaturated monomers having a sulfo group include vinyl sulfonic acid, methallyl sulfonic acid, and p-styrene sulfonic acid. The monomers may be used in the form of salts such as alkali metal salts (e.g., sodium, potassium, etc.) and ammonium salts. These may be used alone or in combination of two or more. Among these, methallyl sulfonic acid and salts of methallyl sulfonic acid are preferred, and methallyl sulfonic acid is more preferred.
[0019] Examples of the ethylenically unsaturated monomer having an amino group include ethylenically unsaturated monomers having a primary amino group, ethylenically unsaturated monomers having a secondary amino group, ethylenically unsaturated monomers having a tertiary amino group, quaternary salts of these ethylenically unsaturated monomers, etc. These may be used alone or in combination of two or more kinds.
[0020] Examples of the ethylenically unsaturated monomer having a primary amino group include vinylamine, allylamine, etc. These may be used alone or in combination of two or more kinds.
[0021] Examples of ethylenically unsaturated monomers having a secondary amino group include diallylamine, etc. These may be used alone or in combination of two or more kinds.
[0022] Examples of ethylenically unsaturated monomers having a tertiary amino group include (meth)acrylates having a tertiary amino group such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate, and (meth)acrylamides having a tertiary amino group such as N,N-dimethylaminopropyl (meth)acrylamide and N,N-diethylaminopropyl (meth)acrylamide. These may be used alone or in combination of two or more.
[0023] The quaternary salt of these monomers means a compound obtained by reacting the ethylenically unsaturated monomer having a primary amino group, the ethylenically unsaturated monomer having a secondary amino group, or the ethylenically unsaturated monomer having a tertiary amino group with a quaternary agent, and the quaternary salt may be an inorganic acid salt such as a hydrochloride or a sulfate, or an organic acid salt such as an acetate. Examples of the quaternary agent include methyl chloride, benzyl chloride, dimethyl sulfate, epichlorohydrin, and the like. These may be used alone or in combination of two or more.
[0024] Among these, it is preferable to contain a (meth)acrylate having a tertiary amino group and / or a quaternary salt of the (meth)acrylate. Note that "(meth)acrylate" means methacrylate and / or acrylate (hereinafter the same).
[0025] The molar ratio of the (a2) component is preferably 0.1 to 30 mol %, more preferably 0.5 to 15 mol %, and even more preferably 0.5 to 5 mol %, relative to 100 mol % of all polymerization components, from the viewpoint of easily suppressing thickening or gelation due to an excessive reaction of the (a1) component during polymerization.
[0026] In the component (a2), the molar ratio of the ethylenically unsaturated monomer having a carboxy group is preferably 0.1 to 30 mol %, more preferably 0.5 to 10 mol %, and even more preferably 0.5 to 5 mol %, based on 100 mol % of all polymerizable components.
[0027] In the component (a2), the molar ratio of the ethylenically unsaturated monomer having a sulfo group is preferably 0.1 to 30 mol %, more preferably 0.5 to 10 mol %, and even more preferably 0.5 to 5 mol %, based on 100 mol % of all polymerizable components.
[0028] In the component (a2), the molar ratio of the ethylenically unsaturated monomer having an amino group is preferably 0.1 to 30 mol %, more preferably 0.5 to 10 mol %, and even more preferably 0.5 to 5 mol %, based on 100 mol % of all polymerizable components.
[0029] The polymerization components may further contain an ethylenically unsaturated monomer (a3) having a crosslinkable group (hereinafter referred to as component (a3)).
[0030] Examples of the component (a3) include N-alkyl(meth)acrylamides such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and Nt-butyl(meth)acrylamide; N,N-dialkyl(meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, and N,N-diisopropyl(meth)acrylamide; N,N'-alkylenebis(meth)acrylamides such as N,N'-methylenebis(meth)acrylamide and N,N'-ethylenebis(meth)acrylamide; crosslinkable monomers having a triallyl group such as triallyl isocyanurate, triallyl trimellitate, triallylamine, and triallyl(meth)acrylamide; and triazines having a (meth)acryloyl group such as 1,3,5-triacryloyl-1,3,5-triazine and 1,3,5-triacryloylhexahydro-1,3,5-triazine. These may be used alone or in combination of two or more. Among them, N,N-dialkyl(meth)acrylamide is preferred, and N,N-dimethyl(meth)acrylamide is more preferred.
[0031] The molar ratio of the (a3) component is preferably 5 mol % or less, more preferably 0.1 to 3 mol %, and even more preferably 0.5 to 1.5 mol %, based on 100 mol % of all polymerizable components.
[0032] The polymerization components may further include a monomer (a4) (hereinafter referred to as component (a4)) other than the components (a1) to (a3).
[0033] Examples of the (a4) component include polymerizable monomers having an aromatic ring, such as styrene, α-methylstyrene, and vinyltoluene; alkyl (meth)acrylates, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate; vinyl carboxylates, such as vinyl acetate and vinyl propionate; nitriles, such as acrylonitrile; mercaptans, such as 2-mercaptoethanol and n-dodecyl mercaptan; alcohols, such as ethanol, isopropyl alcohol, and n-pentyl alcohol; aromatic compounds, such as α-methylstyrene dimer, ethylbenzene, isopropylbenzene, and cumene; and carbon tetrachloride. These may be used alone or in combination of two or more. The molar ratio of the (a4) component is preferably 10 mol% or less, more preferably 5 mol% or less, and even more preferably 3 mol% or less, based on 100 mol% of the polymerization component.
[0034] In the production of the polymer (A), additives such as organic acids such as acetic acid, propionic acid, butanoic acid, citric acid, succinic acid, oxalic acid, glycolic acid, glyoxylic acid, etc., inorganic acids such as hydrochloric acid, sulfuric acid, phosphoric acid, etc., inorganic acid salts such as sodium sulfate, potassium sulfate, ammonium sulfate, aluminum sulfate, etc., inorganic bases such as sodium hydroxide, potassium hydroxide, calcium hydroxide, etc., starches such as oxidized starch, starch phosphate ester, urea phosphate ester, etherified starch, crosslinked starch, APS-modified starch, enzyme-modified starch, cationic starch, amphoteric starch, etc., polyvinyl alcohol, urea, antifoaming agents, antioxidants, preservatives, and bactericides may be added. These may be used alone or in combination of two or more kinds, and the content thereof is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, based on 100 parts by weight of the total polymer components.
[0035] The polymer (A) of the present invention can be obtained by appropriately adjusting the molar ratio of the components (a1) to (a4).
[0036] The polymer (A) essentially contains the components (a1) and (a2), and can be obtained by polymerizing, as necessary, the components (a3) and (a4) and the additives in a solvent in the presence of a polymerization initiator.
[0037] Examples of the polymerization method include a method using only a dropping polymerization method, a method using only a simultaneous polymerization method (a monomer mixture is charged all at once), and a method in which the simultaneous polymerization method and the dropping polymerization method are combined.
[0038] The dropping polymerization method is a method in which a monomer mixture is dropped into a reaction system in which a solvent such as water has been charged in advance, and examples of the method using only this polymerization method include the following (1) to (3). The dropping may be continuous, or may be stopped midway and allowed to polymerize for a certain period of time before restarting the dropping. (1) Method of adding monomer mixture liquid containing all monomer components dropwise (2) Two or more types of monomer mixtures are prepared separately and then added dropwise at the same time (3) Two or more types of monomer mixtures are prepared separately and then added dropwise in sequence.
[0039] Moreover, examples of a method in which the simultaneous polymerization method and the dropping polymerization method are combined include the following methods (4) to (7). (4) A method in which each monomer mixture is polymerized separately and then each polymer is mixed (5) After completing simultaneous polymerization of one or more monomer mixtures, add the remaining monomer mixture dropwise. (6) A method in which one or more types of monomer mixture are simultaneously polymerized, and the remaining monomer mixture is added dropwise during the polymerization. (7) A method of polymerizing one or more types of monomer mixture by dropwise polymerization, adding the remaining monomer mixture all at once, and then polymerizing simultaneously.
[0040] Examples of the solvent include water, organic solvents, etc. These may be used alone or in combination of two or more kinds.
[0041] Examples of water include tap water, pure water, ultrapure water, ion-exchanged water, industrial water, etc. These may be used alone or in combination of two or more kinds.
[0042] Examples of the organic solvent include alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, sec-butyl alcohol, t-butyl alcohol, isobutyl alcohol, n-hexyl alcohol, n-octyl alcohol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and diacetone alcohol; and ethers such as ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether. These may be used alone or in combination of two or more.
[0043] The content of the solvent is adjusted so that the polymerization concentration is preferably 5 to 50% by weight, more preferably 10 to 35% by weight.
[0044] Examples of the polymerization initiator include persulfates such as ammonium persulfate, potassium persulfate, and sodium persulfate; azo compounds such as 2,2'-azobis(2-amidinopropane) hydrochloride and 2,2'-azobis[2(2-imidazolin-2-yl)propane] hydrochloride; and hydrogen peroxide. These may be used alone or in combination of two or more. Among them, ammonium persulfate, potassium persulfate, and 2,2'-azobis(2-amidinopropane) hydrochloride are preferred from the viewpoint of sufficiently proceeding with the solution polymerization. The method of adding the polymerization initiator may be selected as appropriate from among all at once, divided, or continuous dropwise addition.
[0045] The content of the polymerization initiator is usually about 0.001 to 5 parts by weight, and preferably about 0.01 to 1 part by weight, based on 100 parts by weight of all the polymerization components.
[0046] As for the polymerization conditions, for example, the reaction temperature is usually 50 to 100° C. (preferably 60 to 90° C.) and the reaction time is usually 1 to 10 hours (preferably 1 to 6 hours).
[0047] Regarding the physical properties of the obtained polymer (A), for example, the weight average molecular weight is preferably from 10,000 to 7,000,000, and more preferably from 100,000 to 1,000,000. The "weight average molecular weight" here refers to a value obtained by gel permeation chromatography (GPC).
[0048] The viscosity of the polymer (A) is preferably 100 to 20,000 mPa s, and more preferably 500 to 5,000 mPa s. The "viscosity" here refers to the value measured with a B-type viscometer on a solution having a non-volatile content of 20% by weight and adjusted to a temperature of 25°C.
[0049] The polymer (A) may be used alone or in combination of two or more different types of (A) components which have been separately produced.
[0050] The content of the component (A) is preferably 40% by weight or more, more preferably 50 to 80% by weight, and even more preferably 65 to 80% by weight, relative to 100% by weight of the heat-sealable resin composition, because the cured product is likely to exhibit high heat seal strength.
[0051] The heat-sealable resin composition of the present invention may further contain a plasticizer (B) so that the cured product can easily exhibit high heat seal strength. By containing the component (B), the composition can be cured even at a relatively low temperature, and the obtained cured product exhibits high heat seal strength.
[0052] Examples of component (B) include polyols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, glycerol, and glycerin; sugars such as glucose, sucrose, fructose, galactose, and xylose; sugar alcohols such as erythritol, xylitol, maltitol, mannitol, and sorbitol; urea compounds such as urea and urea esters; inorganic acids such as hydrochloric acid and sulfuric acid; inorganic acid salts such as ammonium nitrate and calcium chloride; metal hydroxides such as sodium hydroxide and potassium hydroxide; and organic acid esters such as dibutyl phthalate, dibutyl adipate, and dibutyl sebacate. These may be used alone or in combination of two or more.
[0053] The content of the (B) component is preferably 60% by weight or less, more preferably 20 to 50% by weight, and even more preferably 20 to 35% by weight, relative to 100% by weight of the heat-sealable resin composition, from the viewpoints of making it easy to apply to a substrate and making the cured product likely to exhibit high heat seal strength.
[0054] The weight ratio of the component (A) to the component (B) [(A) / (B)], in terms of non-volatile weight, is preferably [(A) / (B)]=40 / 60 to 100 / 0, more preferably 50 / 50 to 80 / 20, and even more preferably 65 / 35 to 80 / 20, from the viewpoint of achieving both performance expression and coatability.
[0055] The heat-sealable resin composition of the present invention may further contain the above-mentioned solvent. The content of the solvent is preferably adjusted so that the non-volatile content is 15 to 40% by weight, more preferably 20 to 30% by weight.
[0056] The heat-sealable resin composition of the present invention may further contain additives such as pigments, water retention agents, defoamers, preservatives, leveling agents, colorants, antiblocking agents, antioxidants, UV absorbers, thickeners, emulsifiers, dispersants, fillers, etc. These may be used alone or in combination of two or more.
[0057] The viscosity of a solution of the heat-sealable resin composition having a non-volatile content of 20% by weight at a temperature of 25° C. is preferably 50 to 1,000 mPa·s, and more preferably 300 to 800 mPa·s. The viscosity here is a value measured with a B-type viscometer.
[0058] The cured product of the present invention is made of a heat-sealable resin composition.
[0059] The cured product of the present invention can be obtained, for example, by a method in which the heat-sealable resin composition is applied to at least one surface of a substrate and then dried.
[0060] The laminate can be obtained, for example, by applying a heat-sealable resin composition to at least one surface of a substrate and drying the composition.
[0061] Examples of the substrate include base paper, support film, and metal plate.
[0062] Examples of base paper include chemical pulps such as hardwood pulp (LBKP) and softwood pulp (NBKP); mechanical pulps such as groundwood pulp (GP), refiner ground pulp (RGP), and thermomechanical pulp (TMP); and paper made by various papermaking machines using pulp that has been subjected to DIP, mercerization, and waste paper pulp, etc. More specifically, examples of base paper include bleached kraft paper, unbleached kraft paper, fine paper, medium quality paper, lightly coated paper, coated paper, processed base paper, paperboard, white paperboard, liner, semi-glassine paper, glassine paper, parchment paper, etc. In addition, the pulp may contain pH adjusters such as aluminum sulfate, sulfuric acid, and sodium hydroxide; papermaking chemicals such as sizing agents, paper strength enhancers such as starch and polyacrylamide, and wet strength agents; and fillers such as talc, clay, kaolin, titanium dioxide, and calcium carbonate.
[0063] Examples of the support film include polyimide resins such as polyimide and polyimide-silica hybrid; polyolefin resins such as polyethylene, polypropylene, and cycloolefin polymer; polyester resins such as polyethylene terephthalate, polyethylene naphthalate, polybutylene succinate, polybutylene succinate adipate, polybutylene adipate terephthalate, polyhydroxyalkanoate, and polylactic acid; acrylic resins such as polymethyl methacrylate; fluorine-based resins such as polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), and polyvinylidene fluoride (PVDF); aromatic polyester resins obtained from ethylene terephthalate, phenol, phthalic acid, hydroxynaphthoic acid, and parahydroxybenzoic acid (so-called liquid crystal polymers; manufactured by Kuraray Co., Ltd., "Vextar", etc.); cellulose resins such as acetyl cellulose and cellophane; polystyrene resins, polycarbonate resins, and acrylonitrile-butadiene-styrene resins. These may be used alone or in combination of two or more.
[0064] Examples of the metal plate include aluminum-based metal plates such as aluminum plate, aluminum-plated steel plate, and Al-Si alloy-plated steel plate; zinc-based metal plates such as zinc-plated steel plate, Zn-Fe alloy-plated steel plate, Zn-Co alloy-plated steel plate, Zn-Co-Cr alloy-plated steel plate, Zn-Cr-Ni alloy-plated steel plate, Zn-Cr-Fe alloy-plated steel plate, Zn-Al alloy-plated steel plate, Zn-Mg alloy-plated steel plate, Zn-Al-Mg alloy-plated steel plate, and Zn-Ni alloy-plated steel plate; copper plate, steel plate, titanium plate, stainless steel plate, tin plate, nickel-plated steel plate, chromium-plated steel plate, and phosphate-treated steel plate. These may be used alone or in combination of two or more.
[0065] The base paper, support film or metal plate may further have an anchor layer, a filling layer, a water-resistant layer, an oil-resistant layer, a barrier layer, an antistatic layer or the like provided on one or both sides thereof.
[0066] Examples of methods for applying the heat-sealable resin composition include a bar coater, a knife coater, a size press coater, a roll coater, a reverse roll coater, a curtain coater, a gravure coater, a flexo coater, an air knife coater, a calendar, a gate roll coater, a blade coater, a two-roll size press, and a rod metering machine. The amount of the heat-sealable resin composition applied (based on non-volatile content) is usually 0.1 to 10 g / m. 2 , preferably 1 to 7 g / m 2 It is.
[0067] After coating, the substrate is dried by heat, air blowing, or natural drying. Examples of heat sources include hot air dryers, infrared heaters, rotary dryers, etc. The drying conditions are, for example, a temperature of 80 to 220°C (preferably 100 to 200°C) and a time of 1 second to 180 minutes (preferably 30 seconds to 60 minutes).
[0068] The laminate of the present invention has the cured product of the heat-sealable resin composition on at least one surface of a substrate. The substrate to be used, the coating method, the drying method, etc. are as described above. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, parts and percentages are all by weight unless otherwise specified.
[0070] The following monomers are represented by the following abbreviations: AM: Acrylamide IA: Itaconic acid AA: Acrylic acid SMAS: Sodium methallyl sulfonate DM: N,N-Dimethylaminoethyl methacrylate DMAA: N,N-Dimethylacrylamide AN: Acrylonitrile APS: Ammonium persulfate
[0071] Manufacturing Example 1 125 parts of ion-exchanged water was placed in a reactor equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen gas inlet tube, and two dropping funnels, and oxygen in the reaction system was removed by passing nitrogen gas through the reactor, and the reactor was heated to 85°C. Separately, 400 parts of a 50% AM aqueous solution, 19.3 parts of IA, and 200 parts of ion-exchanged water were placed in a dropping funnel (1). In addition, 0.1 parts of APS and 90 parts of ion-exchanged water were placed in a dropping funnel (2). Next, the mixture was dropped into the reactor from the dropping funnel (1) and the dropping funnel (2) over a period of 3 hours. After the dropping, 0.1 parts of APS and 10 parts of ion-exchanged water were placed in the reactor, polymerized for 1 hour, and cooled to obtain a polymer (A-1).
[0072] Manufacturing Examples 2 to 10, Comparative Manufacturing Example 1 Polymers (A-2) to (A-10) were obtained in the same manner as in Production Example 1, except that the compositions of the polymerization components were changed to those shown in Table 1. The polymer in Comparative Production Example 1 was not evaluated because it gelled due to viscosity increase during production.
[0073] [Table 1]
[0074] Example 1 Polymer (A-1) 100 parts (non-volatile content: 26 parts), urea 6.5 parts (non-volatile content: 6.5 parts) and ion-exchanged water 56 parts were mixed to obtain a heat-sealable resin composition with a non-volatile content concentration of 20%. The physical properties of the heat-sealable resin composition are shown in Table 2 (same below).
[0075] Examples 2 to 10 In Example 1, the polymers were changed to (A-2) to (A-10), and ion-exchanged water was added so as to obtain the nonvolatile content concentrations shown in Table 2, thereby obtaining heat-sealable resin compositions.
[0076] Example 11 In Example 6, the weight ratio of polymer (A-6) to urea (in terms of non-volatile content) was changed to 40 / 60, and ion-exchanged water was added so as to obtain the non-volatile content concentration shown in Table 2, thereby obtaining a heat-sealable resin composition.
[0077] Examples 12 and 13 In Example 7, the weight ratio of polymer (A-7) to urea (in terms of non-volatile content) was changed to 65 / 35 and 50 / 50, respectively, and ion-exchanged water was added so as to obtain the non-volatile content concentration shown in Table 2, thereby obtaining a heat-sealable resin composition.
[0078] Example 14 In Example 7, urea was not added, and ion-exchanged water was added so as to achieve the non-volatile content concentration shown in Table 2, thereby obtaining a heat-sealable resin composition.
[0079] Example 15 In Example 10, the weight ratio of polymer (A-10) and urea (in terms of non-volatile content) was changed to 50 / 50, and ion-exchanged water was added so as to obtain the non-volatile content concentration shown in Table 2, thereby obtaining a heat-sealable resin composition.
[0080] Example 16 In Example 1, urea was changed to glycerin, and ion-exchanged water was added so as to achieve the non-volatile content concentration shown in Table 2, thereby obtaining a heat-sealable resin composition.
[0081] <Preparation of Laminate> Evaluation Examples 1-1 to 1-16 Kraft paper (product name: "HEIKO", manufactured by Shimojima Co., Ltd., basis weight 70 g / m 2 ) using a Mayer bar, the heat-sealable resin compositions of Examples 1 to 16 were dried to a non-volatile content of 7 g / m 2 After coating, each layer was dried at 130° C. for 30 seconds to obtain a laminate.
[0082] <Heat seal strength> Each laminate was cut to 75 mm length x 110 mm width and folded in half lengthwise with the coated side facing inward. The folded side was sealed 20 mm from the edge using a heat seal tester TP-701S (manufactured by Tester Sangyo Co., Ltd.) at a temperature of 130°C and a pressure of 2 kgf / cm. 2 The specimen was then heat-pressed for one second. This was then divided into five equal parts to create five test pieces measuring 15mm x 55mm. Each test piece was opened 180° with the sealed area in the center, and pulled vertically using a Tensilon universal testing machine (device name: "RTG1210", manufactured by A&D Co., Ltd.) with a gripping distance of 30mm and a peeling speed of 300mm / min to measure the maximum load. The average value for the five test pieces was taken as the heat seal strength (unit: N / 15mm). The results are shown in Table 2.
[0083] [Table 2]
[0084] (Additional evaluation: Uses a composition that shows a heat seal strength of 2.5N / 15mm in Table 2) Evaluation Examples 2-1 to 2-14 In the preparation of the laminate described above, the heat-sealable resin compositions of Examples 1 to 10, 12, 13, 15 and 16 were applied and then dried at 110°C to obtain a laminate. The heat seal strength of the obtained laminate was measured in the same manner. The results are shown in Table 3.
[0085] [Table 3]
[0086] The results in Table 3 show that the cured product obtained even at a temperature of 110°C exhibited high heat seal strength.
Claims
1. (Meth)acrylamide (a1), and A heat-sealable resin composition comprising a polymer (A) of a polymerization component containing one or more monomers (a2) selected from an ethylenically unsaturated monomer having a carboxy group, an ethylenically unsaturated monomer having a sulfo group, and an ethylenically unsaturated monomer having an amino group.
2. 2. The heat-sealable resin composition according to claim 1, wherein the (a1) component is 60 to 99.5 mol % and the (a2) component is 0.1 to 30 mol % based on 100 mol % of all polymerized components.
3. The heat-sealable resin composition according to claim 1, further comprising a plasticizer (B).
4. A cured product of the heat-sealable resin composition according to any one of claims 1 to 3.
5. A laminate having the cured product according to claim 4 on at least one surface of a substrate.
Citation Information
Patent Citations
Aqueous dispersion and aqueous heat-sealing agent
JP2006045313A